1988
DOI: 10.1002/j.1460-2075.1988.tb03283.x
|View full text |Cite
|
Sign up to set email alerts
|

A mycoplasma high-affinity transport system and the in vitro invasiveness of mouse sarcoma cells.

Abstract: FS9 mouse sarcoma cells were previously shown to be highly invasive when confronted with chicken heart fibroblasts using Abercrombie's confronted explant technique. This invasion could be inhibited by addition to the assay of Fab fragments of a monoclonal antibody directed against p37, a protein associated with the surface of FS9 cells. We have cloned and sequenced the gene for p37. We show that it originates from Mycoplasma hyorhinis and that UGA is a tryptophan codon in this organism. We present evidence tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
105
0
1

Year Published

1988
1988
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(107 citation statements)
references
References 38 publications
1
105
0
1
Order By: Relevance
“…A signal peptide, 23 amino acids in length, is present at the N-terminal of p37. These amino acids direct p37 to the cell outer membrane of M. hyorhinis [4] and p37 is exposed to host proteins when the bacterium infects eukaryotic cells. The signal peptide may guide the exportation of p37 protein from the host eukaryotic cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A signal peptide, 23 amino acids in length, is present at the N-terminal of p37. These amino acids direct p37 to the cell outer membrane of M. hyorhinis [4] and p37 is exposed to host proteins when the bacterium infects eukaryotic cells. The signal peptide may guide the exportation of p37 protein from the host eukaryotic cells.…”
Section: Discussionmentioning
confidence: 99%
“…p37, a part of homologous high-affinity transport system in Mycoplasma hyorhinis [4,11], is known to enhance the invasiveness of melanoma (C8161 and A375M) and prostate carcinoma (PC-3 and Du-145) [6,12]. The colony-forming abilities of AGS and HEK 293T cells are greatly improved by p37 (unpublished data); however, the precise mechanism is still unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exact match primers specific for sequence positions 2071-2090 and 2403-2422, and sequence positions 2972-2991 and 3431-3450 as described in Ref. 9, were used to target p29 and p69 open reading frames using an annealing temperature of 50 C.…”
Section: Methodsmentioning
confidence: 99%
“…The fact that these peculiarities of the nucleotide sequence are characteristic of mycoplasmal gene sequences (10) led us to investigate the possibility that p40 represents a contaminating mycoplasmal protein. A literature search revealed that p40 is virtually identical to p37, which is one component of an operon determining a mycoplasmal membrane transport system for Mycoplasma hyorhinis (9).…”
Section: Methodsmentioning
confidence: 99%